Mechanisms and predictability of multiyear ecosystem variability in the North Pacific. Issue 11 (30th November 2015) - Chikamoto, Megumi O.; Timmermann, Axel; Chikamoto, Yoshimitsu; Tokinaga, Hiroki; Harada, Naomi
Abstract: Aleutian Low variations provide vorticity, buoyancy, and heat‐flux forcing to the North Pacific Ocean, which in turn cause changes in ocean circulation, mixed layer characteristics and sea ice coverage. In this process the white noise atmospheric characteristics are integrated dynamically and thermodynamically to generate red noise ocean spectra. Using the Community Earth System Model (version 1.0.3) we study the resulting biogeochemical and ecosystem responses in the North Pacific. We find that ocean dynamical variables have an impact on the tendencies of key nutrients and biological production, which leads to a further reddening of biogeochemical spectra resulting in potential predictability on time scales of 2–4 years. However, this low‐pass filtering does not apply to all biogeochemical variables and is regionally dependent. It is shown that phytoplankton biomass in the Central North Pacific adjusts to the much shorter‐term variability associated with changes in mixed layer depth, light availability, and zooplankton grazing, thus limiting the predictability of phytoplankton anomalies to about 1 year. In the eastern North Pacific the slow advection of anomalous nutrient concentrations leads to longer persistence of phytoplankton variability and increased potential predictability of up to 3 years. Key Points: Aleutian Low variability generates short and long ecosystem responses North Pacific nutrients and biological production have multiyear memory and predictability